Bioethics in the Oversight of Clinical Research: Institutional Review Boards and Data and Safety Monitoring Boards - Grady, Christine (Kennedy Institute of Ethics journal, 2019)
, ABSTRACT:, This article describes oversight mechanisms for clinical research that have developed substantially over the last few decades, including institutional review boards and data safety and monitoring boards. LeRoy Walters and others in the 1970s in the US thoughtfully described the importance of fundamental ethical principles and the application of bioethics to clinical research. Dr. Walters’s important essay and work with the National Commission for the Protection of Human Subjects of Biomedical and Behavioral Research helped identify and explain ethical principles that guide research. These principles, subsequently enunciated by the Commission in the Belmont Report, remain central to our understanding of the ethics of clinical research and are the foundation of our regulations. In this article, I review some history, successes, and challenges of IRBs and DSMBs to exemplify the significance of understanding and applying ethical principles to the design and conduct of clinical research, and to honor Dr. Walters’s contributions.